Development of human innate immune responses in a humanized mouse model expressing four human myelopoiesis transgenes - Stocks, Hannah; De Leeuw, Elisabeth; Lambrecht, Bart N.; Vandekerckhove, Linos; van Loo, Geert; Wullaert, Andy (Frontiers in Immunology, 2024)
Background Dysregulated innate immune responses underlie multiple inflammatory diseases, but clinical translation of preclinical innate immunity research in mice is hampered by the difficulty of studying human inflammatory reactions in an in vivo context. We therefore sought to establish in vivo human inflammatory responses in NSG-QUAD mice that express four human myelopoiesis transgenes to improve engraftment of a human innate immune system.We reconstituted NSG-QUAD mice with human hematopoietic stem and progenitor cells (HSPCs), after which we evaluated human myeloid cell development and subsequent human responses to systemic and local lipopolysaccharide (LPS) challenges.Results NSG-QUAD mice already displayed engraftment of human monocytes, dendritic cells and granulocytes in peripheral blood, spleen and liver at 6 weeks after HSPC reconstitution, in which both classical, intermediate and non-classical monocytes were present. These huNSG-QUAD mice responded to intraperitoneal and intranasal LPS challenges with production of NF-κB-dependent human cytokines, a human type I interferon response, as well as inflammasome-mediated production of human IL-1β and IL-18. The latter were specifically abrogated by the NLRP3 inhibitor MCC950, while LPS-induced human monocyte death was not altered. Besides providing proof-of-principle for small molecule testing of human inflammatory reactions in huNSG-QUAD mice, this observation suggests that LPS-induced in vivo release of human NLRP3 inflammasome-generated cytokines occurs in a cell death-independent manner.HuNSG-QUAD mice are competent for the NF-κB, interferon and inflammasome effectors of human innate immunity, and can thus be utilized to investigate signaling mechanisms and pharmacological targeting of human inflammatory responses in an in vivo setting.